Managing time in the rice-based cropping systems: Gender responsive approach and strategy - Munshi, Sugandha; Samaddar, Arindam; Srivastava, Amit; Yadav, Anil Kumar; Sohane, R. K.; Patil, Vikram; Peramaiyan, Panneerselvam; Kumar, Virender (International Rice Reseach Institute, 2025)
Climate change is a pressing issue of current time and when it comes to agriculture it directly affects the agriculture production and the entire agriculture system. It is not gender neutral, affecting men and women differently. Hence, it becomes imperative to have gender responsive approach while designing and implementing innovations and solutions addressing the issue. 80% of the rice-growing areas in easter India specifically are rain-fed and thus suffer either from excess water or from drought depending upon rainfall pattern. Unpredictable monsoon further adds to the problem for farmers across the region. As a result, it becomes important to cater to the need of farmers tackling the climate change repercussion on their farm productivity. Time management of planting dates in rice and wheat has been identified as a promising solution to this problem.